Midterm survival of imaging-assisted robotic lung segmentectomy for non-small-cell lung cancer. (23rd October 2021) - Chaari, Zied; Montagne, François; Sarsam, Matthieu; Bottet, Benjamin; Rinieri, Philippe; Gillibert, Andre; Baste, Jean Marc
Abstract: OBJECTIVES: Our goal was to report our midterm results using imaging-assisted modalities with robotic segmentectomies for non-small-cell lung cancer (NSCLC). METHODS: This was a retrospective study of all robotic segmentectomies, with confirmed NSCLC, performed at our general and thoracic surgery unit in the Rouen University Hospital (France), from January 2012 through December 2019. Benign and metastatic lesions were excluded. Data were extracted from the EPITHOR French nationwide database. RESULTS: A total of 121 robotic segmentectomies were performed for 118 patients with a median age of 65 (interquartile range: 60, 69) years. The majority had clinical stage T1aN0M0 (71.9%) or T1bN0M0 (13.2%). The mean (standard deviation) number of resected segments was 1.93 (1.09) with 80.2% imaging-assisted segmentectomies. Oriented (according to tumour location) or systematic lymphadenectomy or sampling was performed for 72.7%, 23.1% and 4.1% of patients. The postoperative course was uneventful for 94 patients (77.7%), whereas 34 complications occurred for 27 patients (22.3%), including 2 patients (1.7%) with Clavien-Dindo ≥III complications. The mean thoracic drainage duration was 4.12 days, and the median hospital stay was 4 days (interquartile range: 3, 5) after the operation. The 2-year survival rate was 93.9% (95% confidence interval: 86.4–97.8%). Excluding stage IV ( n = 3) and stage 0 tumours ( n = 6), the 2-year survival rate was 95.7% (95% confidence interval: 88.4–98.8%) compared to an expected survival rate of 94.0% according to stage-specific survival rates found in a large external reference cohort. CONCLUSIONS: Imaging-guided robotic-assisted thoracic surgery segmentectomy seems to be useful and oncological with good midterm results, especially for patients with early-stage NSCLC. Abstract : Anatomical resection is the standard treatment for early-stage non-small-cell lung cancer (NSCLC).